2016
DOI: 10.1177/0269881116672342
|View full text |Cite
|
Sign up to set email alerts
|

The frontal cortex as a network hub controlling mood and cognition: Probing its neurochemical substrates for improved therapy of psychiatric and neurological disorders

Abstract: The highly-interconnected and neurochemically-rich frontal cortex plays a crucial role in the regulation of mood and cognition, domains disrupted in depression and other central nervous system disorders, and it is an important site of action for their therapeutic control. For improving our understanding of the function and dysfunction of the frontal cortex, and for identifying improved treatments, quantification of extracellular pools of neuromodulators by microdialysis in freely-moving rodents has proven indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 267 publications
(536 reference statements)
0
27
0
Order By: Relevance
“…Large numbers of studies have confirmed that the metabolic disorders of monoamine neurotransmitters are closely related to a series of neurodegenerative diseases, which have been recognized to play major regulatory roles in cognitive function (Bouwmans, Leentjens, Mess, & Weber, ; Millan, Rivet, & Gobert, ; Tadaiesky et al, ), where Trp metabolism has been singled out to be one of the important branches. Trp, a significant precursor for the synthesis of neurotransmitters in the human body, can adjust the mental rhythm and improve sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large numbers of studies have confirmed that the metabolic disorders of monoamine neurotransmitters are closely related to a series of neurodegenerative diseases, which have been recognized to play major regulatory roles in cognitive function (Bouwmans, Leentjens, Mess, & Weber, ; Millan, Rivet, & Gobert, ; Tadaiesky et al, ), where Trp metabolism has been singled out to be one of the important branches. Trp, a significant precursor for the synthesis of neurotransmitters in the human body, can adjust the mental rhythm and improve sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of studies have confirmed that the metabolic disorders of monoamine neurotransmitters are closely related to a series of neurodegenerative diseases, which have been recognized to play major regulatory roles in cognitive function (Bouwmans, Leentjens, Mess, & Weber, 2016;Millan, Rivet, & Gobert, 2016;Tadaiesky et al, 2008),…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we compared the glycine modulatory site agonists (glycine, D-serine, D-cycloserine and S18841) and GlyT1 inhibitors (sarcosine and ORG25935) on microdialysis levels of glycine and D-serine and other neurotransmitters thought to regulate cognition in the prefrontal cortex (PFC) of rats [37]. These compounds were also compared in three cognitive tasks: social recognition, novel object recognition (NOR) and an associative conditioned freezing response (CFR) task (selected for translational relevance to schizophrenia from consensus reviews [38,39], and whose predictive validity will be considered in the discussion). In addition, we employed a microinjection procedure to examine the role of the PFC in the action of S18841.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the substantial fecundity disadvantage of people with a diagnosis of schizophrenia, reduced to about 50% compared to healthy individuals (Crow 1995b, Brune 2004, Power et al 2013, Markow 1994, McGrath et al 1999) and, to finish with a significantly increased risk of mortality compared to healthy individuals (Saha et al 2007, Liu et al 2017, Tsuang and Simpson 1988, Allebeck 1989, Brown 1997, Harris and Barraclough 1998, Olfson et al 2015.…”
Section: The Core Facts Of Schizophreniamentioning
confidence: 99%